HUBUNGAN ANTARA PERILAKU KELUARGA DAN KONDISI LINGKUNGAN DALAM RUMAH DENGAN KEJADIAN PNEUMONIA PADA ANAK BALITA DI WILAYAH KERJA PUSKESMAS HALMAHERA KOTA SEMARANG - Juwita Ayang Nuretza; Suhartono Suhartono; Sri Winarni (Jurnal Kesehatan Masyarakat (Undip), 2017)
Pneumonia inchildren under five years old inIndonesiaisamajorhealthproblem. Accoarding to city health offices Semarang, pneumonia is found in the third greatest number withinthe community health centre working area of Halmahera. In 2016 the occurence of pneumonia in health centre working area of Halmahera was 452 cases (13%), greater than the occurrence of 440 cases (12,7%) in the previous year. The aim of the research is to analyze the relationship between the behavior of family and physical environment condition of the house with pneumonia incidence on children under five years old in health centre working area of Halmahera. This research uses a type of survey research that is analytic observation approach case control. The population in this research was 106. Then obtained total samples of 90 respondent consist of 45 cases groups and 45 control groups. Data was collected by interview, observation, and measurement. Analysis of data using univariate analysis, bivariate analysis with  Chi square test with 95% confidence interval. The results showed that the variables which had significant relationship with pneumonia incidence such as index of natural lighting in the home (p=0,02; OR=3,0; 95%CI=1,3-7,2), exsistence of family members smoked (p=0,001; OR=8,5;95%CI=2,3-31,7), and the habit use mosquito coils (p=0,019; OR=3,6; 95%CI= 1,3-9,9). And variable which had not significant are temperature (p=1,000; OR=1,2; 95%CI=0,4-3,3), the house of humidity (p=0,812; OR=1,3; 95%CI=0,5-3,2) and type of cooking fuel (p=1,000; OR=2,0; 95%CI=0,2-23,4). This conclusion is house physical environment that associated with pneumonia incidence such as type of natural lighting in the home. And the behavior that associated with pneumonia is the exsistence of family members smoked and the habit use mosquito coils.